1990
DOI: 10.4319/lo.1990.35.2.0399
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the hydrogen sulfide‐induced growth limitation in wetland macrophytes

Abstract: Hydrogen sulfide, a phytotoxin that often accumulates in anoxic marine and freshwater marsh soils, suppressed the activity of alcohol dehydrogenase (ADH), the enzyme that catalyzes the terminal step in alcoholic fermentation, in the roots of two wetland macrophytes. This inhibition of root ADH activity with increasing sulfide concentration was associated with decreases in root total adenine nucleotide pool (ATP + ADP + AMP), the adenylate energy charge ratio (AEC), nitrogen uptake (percent recovery of rSNH,+-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
167
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(173 citation statements)
references
References 37 publications
4
167
1
1
Order By: Relevance
“…Hydrogen sulfide, a well-known phytotoxin, can inhibit the anoxic production of ATP and nitrogen uptake in roots (Koch et al, 1990) and can reduce maximum photosynthetic rates (Goodman et al, 1995). Our data indicated that anoxic conditions suppressed net photosynthesis and altered the balance of carbon and nitrogen metabolism (Figs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hydrogen sulfide, a well-known phytotoxin, can inhibit the anoxic production of ATP and nitrogen uptake in roots (Koch et al, 1990) and can reduce maximum photosynthetic rates (Goodman et al, 1995). Our data indicated that anoxic conditions suppressed net photosynthesis and altered the balance of carbon and nitrogen metabolism (Figs.…”
Section: Discussionmentioning
confidence: 80%
“…Sediment anoxia affects plants by regulating respiration and phytotoxin production resulting from anaerobic degradation of organic matter (Koch et al, 1990;Spencer & Ksander, 1995;Holmer & Bondgaard, 2001). Hydrogen sulfide, a well-known phytotoxin, can inhibit the anoxic production of ATP and nitrogen uptake in roots (Koch et al, 1990) and can reduce maximum photosynthetic rates (Goodman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…KEY WORDS: Carbon sequestration · Decomposition · Plant production · Sea-level rise · Long-term ecological research · LTER Resale or republication not permitted without written consent of the publisher 1981), redox conditions (Mendelssohn et al 1981, Mendelssohn & McKee 1988, pore water sulfide concentration (Morris 1980, Koch et al 1990, and nutrient availability (Woodhouse et al 1974, Valiela et al 1976, Morris 1980, Darby & Turner 2008. Low redox conditions stimulate root growth as a stress response to oxidize the rhizosphere, sulfide reduces the plant's ability to take up nitrogen leading to increased root production, and high nutrient availability shifts the plant biomass production from roots to aboveground.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfide exposure correlates with stunted growth in the field (King et al 1982) and results in reduced growth, alcohol dehydrogenase activity, adenylate charge, and nitrogen uptake in laboratory experiments (Koch and Mendelssohn 1989;Koch et al 1990). Although sensitive to sulfide, S. alterniflora is more tolerant of sulfide than are other freshwater marsh species that do not encounter elevated sulfide (Koch and Mendelssohn 1989;Koch et al 1990). Thus, it is apparent that while sulfide is an important environmental stressor of S. alterniflora, physiological mechanisms of sulfide tolerance may be exhibited.…”
mentioning
confidence: 99%
“…Environmental sulfide enters the root tissues (Carlson and Forrest 1982) and can inhibit metalloenzymes, including cytochrome c oxidase (Allam and Hollis 1972;Havill et al 1985). Sulfide exposure correlates with stunted growth in the field (King et al 1982) and results in reduced growth, alcohol dehydrogenase activity, adenylate charge, and nitrogen uptake in laboratory experiments (Koch and Mendelssohn 1989;Koch et al 1990). Although sensitive to sulfide, S. alterniflora is more tolerant of sulfide than are other freshwater marsh species that do not encounter elevated sulfide (Koch and Mendelssohn 1989;Koch et al 1990).…”
mentioning
confidence: 99%